Social workers’ perceptions on clients’ service needs and social work practices during the COVID-19 pandemic - Mesiäislehto, Merita; Kivipelto, Minna; Hiilamo, Heikki (Journal of Comparative Social Work, 2021)
Ever since the start of the COVID-19 pandemic, the specialized health-care resources have been the main focus of political attention in any country. However, the pandemic and subsequent lockdowns have also had a major impact on social services. The pandemic increased service needs among those who were already adult social work clients before the pandemic; it also created needs among new groups of clients, while the operating environment for service provision changed dramatically. In our study, we examine social workers’ perceptions on: 1) how well social services were able to respond to clients’ needs during the pandemic; and 2) examine practices in adult social work that were used and developed during the outbreak of the pandemic. For the analysis, we use national survey data obtained from social workers in the Social Barometer survey collected in May 2020 (n=496) and in January 2021 (n=412). The findings show that according to social workers, during the first year of the pandemic social work in Finland succeeded in responding to clients’ rather clear and concrete problems, such as difficulties in applying for social benefits and a lack of housing, while more complicated problems, such as unmanageable debts, loneliness and mental health problems, were not adequately responded to. At the same time, social workers assessed that people suffering from these problems were the most affected by the COVID-19 pandemic.